Protectionism under R&D policy: innovation rate and welfare - de Mello-Sampayo, F.; Sousa-Vale, S.; Camões, F.; Gomes, O. (Journal of Economic Studies, 2012)
Purpose – The purpose of this paper is to explain how eventual pressures from national lobbies may lead governments to shift from an optimal into a non?optimal innovation policy. Design/methodology/approach – A theoretical model is developed in order to examine and explain the growth and welfare effects of optimal and non?optimal innovation policies. The non?optimal policy corresponds to a subsidy for national innovators that is equivalent to an optimal policy of incentives (tax cuts) to foreign investors. Since we are assessing what can nationals do with the support that could be oriented to foreign firms, we are measuring what the economy loses for not supporting foreign firms. Findings – The authors find welfare loss when supporting national R&D instead of foreign R&D and conclude that the same support given to innovation can produce strikingly different outcomes depending on who receives the support. Practical implications – The analysis allows the impact of the inefficiency caused by policies that are not sound, from a strictly economic point of view, to be measured. Originality/value – The originality of the paper is related to the assessment of the implications and to the measurement of the effects of non?optimal R&D policies.